Analysis of Healthcare Utilization for Primary Dysmenorrhea in Korea: A Retrospective, Cross-Sectional Study - Park J; Lim YC; Hwang DS; Ha IH; Lee YS (Dove Medical Press, 2022)
Jinhun Park,1 Yu-Cheol Lim,2 Deok-Sang Hwang,3 In-Hyuk Ha,2 Ye-Seul Lee2 1Department of Internal Medicine, Jaseng Hospital of Korean Medicine, Seoul, Republic of Korea; 2Jaseng Spine and Joint Research Institute, Jaseng Medical Foundation, Seoul, Republic of Korea; 3Department of OB & GY in Korean Medicine, College of Korean Medicine, Kyung Hee University, Seoul, Republic of KoreaCorrespondence: In-Hyuk Ha; Ye-Seul Lee, Jaseng Spine and Joint Research Institute, Jaseng Medical Foundation, 2F, 540 Gangnam-daero, Gangnam-gu, Seoul, 06110, Republic of Korea, Tel +82-2-2222-2740, Fax +82-2-2222-2737, Email hanihata@gmail.com; yeseul.j.lee@gmail.comPurpose: This study is a retrospective, cross-sectional study aiming to present basic data on the treatment modalities and cost of care for primary dysmenorrhea (PD) by analyzing healthcare utilization and patient distributions using the 2010 to 2018 Health Insurance Review and Assessment Service (HIRA) data.Patients and Methods: We used the HIRA-National Patient Sample (NPS) data to analyze medical service utilization for PD (ICD-10 code: N94.4, N94.6) in Western medicine (WM) or Korean medicine (KM) care between January 2010 and December 2018.Results: There were 41,139 patients diagnosed with PD who utilized Western medicine (WM) or Korean medicine (KM) care at least once during the study period. The number of claims and patients steadily rose over the years from 7430 claims for 3989 patients in 2010 to 11,523 claims for 6226 patients in 2018. The predominant age group was 15 to 24 years. Regarding the frequency of service categories for PD in the claims, consultation was the most common and costly service category in WM (72,120 cases, 47.89%; 631,912 USD, 69.74%), while injection and analogous treatments was the most common and costly service category in KM (97,157 cases, 72.41%; 314,696 USD, 55.86%). Regarding the drug prescriptions, nonsteroidal anti-inflammatory drugs (NSAIDs) (26,617 cases, 40.47%) were the most frequently prescribed drug for PD in pharmacies and hospitals.Conclusion: The result shows an annual increase in healthcare utilization for PD with the fastest rate in individuals aged 15 to 24 years. This study provides data on the current utilization of WM and KM care for PD for policymakers. Furthermore, we analyzed the frequency and cost of common treatment modalities in WM and KM, which would be useful data for clinicians and researchers.Keywords: primary dysmenorrhea, healthcare administrative claims, health care costs, medical use